How flies are flirting on the fly. Issue 1 (December 2017) - Eichorn, Courtney; Hrabar, Michael; Van Ryn, Emma; Brodie, Bekka; Blake, Adam; Gries, Gerhard
Abstract Background Flies have some of the most elaborate visual systems in the Insecta, often featuring large, sexually dimorphic eyes with specialized "bright zones" that may have a functional role during mate-seeking behavior. The fast visual system of flies is considered to be an adaptation in support of their advanced flight abilities. Here, we show that the immense processing speed of the flies' photoreceptors plays a crucial role in mate recognition. Results Video-recording wing movements of abdomen-mounted common green bottle flies, Lucilia sericata, under direct light at 15, 000 frames per second revealed that wing movements produce a single, reflected light flash per wing beat. Such light flashes were not evident when we video-recorded wing movements under diffuse light. Males ofL. sericata are strongly attracted to wing flash frequencies of 178 Hz, which are characteristic of free-flying young females (prospective mates), significantly more than to 212, 235, or 266 Hz, characteristic of young males, old females, and old males, respectively. In the absence of phenotypic traits of female flies, and when given a choice between light emitting diodes that emitted either constant light or light pulsed at a frequency of 110, 178, 250, or 290 Hz, males show a strong preference for the 178-Hz pulsed light, which most closely approximates the wing beat frequency of prospective mates. Conclusions We describe a previously unrecognized visual mate recognition system inL. sericata . The system depends upon the sex- and age-specific frequencies of light flashes reflecting off moving wings, and the ability of male flies to distinguish between the frequency of light flashes produced by rival males and prospective mates. Our findings imply that insect photoreceptors with fast processing speed may not only support agile flight with advanced maneuverability but may also play a supreme role in mate recognition. The low mating propensity ofL. sericata males on cloudy days, when light flashes from the wings of flying females are absent, seems to indicate that these flies synchronize sexual communication with environmental conditions that optimize the conspicuousness of their communication signals, as predicted by sensory drive theory.